Being heard on the world stage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Food Rights Campaign Co-ordinator for Action Aid Kenya explains the work that Action Aid is doing to ensure farmers? concerns are heard in World Trade Organisation negotiations. She also encourages farmers to be active in pursuing their interests at a national and international level.